ANALISIS POTENSI DAN PEMANFAATAN AIR WADUK CIPANCUH DI KABUPATEN INDRAMAYU - Suripto Suripto (Politeknik Negeri Jakarta, 2011)
Abstract Analysis is a way to check the availability and irrigation water requirements in an agricultural land. For the purposes of irrigation, enough water is needed to increase agricultural productivity. Performance management of irrigation water at farm level is very varied with irrigation water allocation is less efficient. It is thus this is one major cause actual yields are still low. Then need to arrange for water use and preparation of schedules and appropriate cropping pattern under various conditions. So that would be more effective in using water, expected in the future no water shortage, which in turn will increase productivity pertanian.Yang ultimately to meet national food needs. The research shows that it turns out the availability of water in the reservoir Cipancuh insufficient irrigation water requirements. Keywords : rainfall, dependable flow, cropping patterns and crop species.